Population pharmacokinetic and pharmacodynamic analyses of safinamide in subjects with Parkinson's disease. Issue 5 (8th August 2016) - Loprete, Luca; Leuratti, Chiara; Cattaneo, Carlo; Thapar, Mita M.; Farrell, Colm; Sardina, Marco
Abstract: Safinamide is an orally administered α ‐aminoamide derivative with both dopaminergic and non‐dopaminergic properties. Nonlinear mixed effects models for population pharmacokinetic (PK) and pharmacokinetic–pharmacodynamic (PKPD) analyses were developed using records from, respectively, 623 and 668 patients belonging to two Phase 3, randomized, placebo‐controlled, double‐blind efficacy studies. The aim was to estimate safinamide population PK parameters in patients with Parkinson's disease (PD) on stable levodopa therapy, and to develop a model of safinamide effect on the PD phase of normal functioning (ON‐time). The final models were internally evaluated using visual predictive checks (VPCs), prediction corrected‐VPC, and nonparametric bootstrap analysis. Safinamide profiles were adequately described by a linear one‐compartmental model with first‐order absorption and elimination. CL/F, Vd/F, and KA (95% confidence interval [CI]) were 4.96 (4.73–5.21) L/h, 166 (158–174) L, and 0.582 (0.335–0.829) h −1, respectively. CL/F and Vd/F increased with body weight, while age, gender, renal function, and exposure to levodopa did not influence safinamide PK. The observed ON‐time values were adequately described by a linear model, with time in the study period as dependent variable, and rate of ON‐time change and baseline plus offset effect as slope and intercept parameters. Safinamide treatment resulted in an increase in ON‐time of 0.73 h (week 4), with further ON‐time increase with the same slope as placebo. The increase was not influenced by age, levodopa, or safinamide exposure. The population models adequately describe the population PK of safinamide and safinamide effect on ON‐time. No dose adjustments in elderly and mild to moderate renally impaired patients are requested.